Adaptive sensor data acquisition for gait analysis - Kilian, W.; Hill, M.; Odenwald, S. (Procedia Engineering, 2016)
In this paper a method is presented that uses one sensor configuration for both static and dynamic loading conditions to capture plantar pressure distribution values. In the gait analysis, different phases are from interest. The phases produces highly different signals and with conventional sensors and static data acquisition systems it is often difficult to achieve high precision measure- ments. An advanced programmable amplifier can be used to adapt the full resolution of the measurement system dynamically to the needs of the gait analyses. With the proposed system, it is possible to precisely measure the gait phases without changing any hardware. While the system is performing it is energy efficient as it only consumes power if needed. Furthermore, it is highly integrated and space saving. Thus, ideally suited for mobile outdoor applications. The technology used in this example can be applied to many different general sensor measurement questions in sports engineering.